Political and technological changes, glass provenance and a new glass production model along the west Asian Silk Road - Henderson, Julian; Chenerya, Simon; Fabera, Edward W.; Krögerd, Jens (Topoi, 2021)
We consider some of the social, political, and economic factors that led to the mass production of glass, especially during the ‘Abbasid Caliphate. Scientific analysis is used to investigate glass production, and consider how these factors can be used to interpret the results having defined glass technology and its provenance for glass derived from a 2000-mile area of the Middle East, between Egypt and northern Iran. The results show evidence of production in the Levant, northern Syria, and Iran/Iraq as well as sub-zones associated with cosmopolitan urban centers in Cairo, Beirut, Damascus, Al-Raqqa, Samarra, Ctesiphon, and Nishapur and specialized production of specific vessel types. It is shown that glass trade occurred between these hubs with limited recycling within a decentralized production system forming part of the ‘Abbasid economic boom.